Maximizing the link throughput between smart meters and aggregators as secondary users under power and outage constraints - Nardelli, Pedro H. J.; Tome, Mauricio de Castro; Alves, Hirley; Lima, Carlos H. M. de [UNESP]; Latva-aho, Matti (Elsevier B.V., 2016)
This paper assesses the communication link from smart meters to aggregators as (unlicensed) secondary users that transmit their data over the (licensed) primary uplink channel. The proposed scenario assumes: (i) meters' and aggregators' positions are fixed so highly directional antennas are employed, (ii) secondary users transmit with limited power in relation to the primary, (iii) meters' transmissions are coordinated to avoid packet collisions, and (iv) the secondary links' robustness is guaranteed by an outage constraint. Under these assumptions, the interference caused by secondary users in both primary (base-stations) and other secondary users can be neglected. As unlicensed users, however, meter-aggregator links do experience interference from the mobile users of the primary network, whose positions and traffic activity are unknown. To cope with this uncertainty, we model the mobile users spatial distribution as a Poisson point process. We then derive a closed-form solution for the maximum achievable throughput with respect to a reference secondary link subject to transmit power and outage constraints. Our numerical results illustrate the effects of such constraints on the optimal throughput, evincing that more frequent outage events improve the system performance in the scenario under study. We also show that relatively high outage probabilities have little effect on the reconstruction of the average power demand curve that is transmitted from the smart meter to the aggregator. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cognitive network; Poisson point process; Smart grid communication; Spectrum sharing